TEACHING VOCABULARY BY USING PICTURES TO THE SECOND YEAR STUDENTS OF SMP NEGERI 1 EMBALOH HILIR KAPUAS HULU IN ACADEMIC YEAR 2007/2008 - Astuti, Desi Sri (IKIP PGRI Pontianak, 2014)
AbstractThe purpose of this research is to â€œInvestigate whether or not the use ofÂ Â pictures improves the studentsâ€™ mastery of vocabulary of the second year students of SMPN 1 Embaloh Hilir Kapuas Hulu in academic year 2007/2008. The methodology of this research is pre-experimental study design. It is employed and designed with measurement of the students â€œpre-test and post-test total scoresâ€, the students mean score of each test (pre-test and pos-test), and the test of significance. Based on the computation of t-value, the Alternative Hypothesis is accepted and the Null Hypothesis is rejected. Teaching vocabulary by using pictures to theÂ second year students of SMPN 1 Embaloh Hilir Kapuas Hulu in academic year 2007/2008 is able to improve the studentsâ€™ mastery of vocabulary.Â Keyword : pictures, vocabulary